Teacher job satisfaction viewed from the perspective of work motivation and principal performance - Nisaul Khaira; Yusrizal Yusrizal; Niswanto Niswanto (STAI Hubbulwathan Duri, 2022)
This research aims to determine the effect of work motivation and principal's performance on teacher job satisfaction together at a senior high school in … sebutkan nama kota/kabupaten/provinsinya. This research uses a quantitative approach with associative methods. The analysis technique data used is simple and multiple linear regression analysis, t-test, and F test. The results showed that: 1) There is a significant influence between the principal's work motivation on teacher job satisfaction by 79.1%. This means that work motivation will affect the job satisfaction of teachers in schools for the achievement of maximum performance; 2) There is a significant influence between the principal's performance on teacher job satisfaction by 49.7%. Therefore, the two variables can go hand in hand, the better the principal's performance, the better the teacher's job satisfaction; 3) There is a significant influence between work motivation and principal performance on teacher job satisfaction by 81.4%. This means that the two variables, namely work motivation and principal performance, go hand in hand with teacher job satisfaction, meaning that the better the work motivation and performance of the principal, the higher the teacher's job satisfaction.